FACTORS INFLUENCING THE DETERIORATION OF NEW FACILITIES: A QUALITATIVE STUDY AT A PRIVATE HOSPITAL IN MALANG - Cahya Firly Nanda; Nur Rahmah, Shofi; Kuncoro, Wahyudi (Journal of Community Health and Preventive Medicine, 2025)
This study aims to analyze the causes of damage to hospital facilities even though they are still newly used. The research was conducted in one of the private hospitals in Malang City using descriptive qualitative methods by conducting a series of observation activities, focus group discussions (FGDs), in depth interviews with 7 people both previous directors, managers and unit heads in the past period and the current period. Identification of factors affecting damage to building facilities and other utilities in the hospital are: 1.) there is no comprehensive monitoring system on a regular basis from the IPSRS unit, 2.) there is no guide to the construction of facilities in the hospital so that units that should be able to participate in the planning and supervision team of the construction process cannot be carried out in an integrated manner, and 3.) The absence of an inventory system of work equipment IPSRS unit so that equipment is often lost due to various factors. It is expected that by knowing the factors that affect damage to facilities in the hospital, management can anticipate both minimizing the potential for damage at this time, and preventing these factors in the future to make improvements.